Examining learners’ and instructors’ perspectives on the use of blended wiki sessions to improve professionals’ writing skills (BRAC University Journal, 2026)
This paper focuses on the learners’ and instructors’ perspectives on wiki based virtual writing sessions while investigating the effectiveness and challenges of such blending in a demand-driven English language course for mid-level BRAC managers who are in need of improving their English writing skills. It shows how a psychological barrier-free ideal writing environment was created for the managers through DevNet, a wiki spaces based platform, during a eight-week-long course. In particular, this paper assesses the strategies followed to fill the vacuity of instructor’s physical absence and also to involve the participants in collaborative learning. Qualitative data collected from the learners and the instructors through interviews was analyzed to understand learners’ and instructors’ perspectives on virtual writing sessions, to measure the effectiveness of those sessions, and also to identify the challenges in blending information and communication technology (ICT) tools in the English course for the professionals. Findings show that blending of wiki sessions with regular face-to-face (F2F) classroom sessions significantly improves learners’ writing skills and helps them to reflect on their classroom sessions by using own language, commenting on peer posts, arguing against peer-views as well as appreciating good writing and new ideas. This paper emphasizes the need of synchronous instruction, thought-igniting deferential feedback and parallel arrangement of the wiki-session contents with F2F classroom sessions to help learners develop their writing. Opportunity for asynchronous activities, however, always remains valid because of the comparative permanence of the written posts in the DevNet. The paper also highlights how similar strategies can be adopted, especially for professionals, through ICT-based media in a fast-changing web-based era.